Exploring the Defense Mechanisms of the Main Character in The Accidental Tourist After the Shooting Tragedy - Lintang Cahyani; Sri Sumaryani (Universitas Islam Negeri Palopo, 2025)
In the United States, numerous mass shootings have left victims and their families traumatized. Authors have been inspired to create literary works based on this phenomenon. One of these can be found in Anne Tyler's book The Accidental Tourist, first published in 1985. The novel narrates the tale of a father who must cope with anxiety following the death of his only child, caused by a school shooting tragedy. This study aims to find the types of defense mechanisms performed by the father as attempts to protect himself against the threat of experiencing anxious feelings from things that could trigger thoughts of his trauma. This study used Freud's theory of defense mechanisms, which includes denial, displacement, rationalization, and reaction formation. The primary data obtained from the novel in the form of dialogue will be compared to the data collected through several previous studies using a qualitative approach to be categorized according to Freud's theory of defense mechanisms. The study's findings indicate that the main character employs four defense mechanisms to maintain his image as a husband that aligns with social standards and expectations. The main character employs four defenses in five dialogues in the novel. The appearance of four defense mechanisms is also influenced by the main character's roles as a husband who struggles to meet social standards as a strong and more mature person compared to his wife. Men are expected to manage their stress on their own and avoid expressing their emotions according to the social standards surrounding masculinity. This leads men to use defense mechanisms.